Electrical Resistivity of the Y(Ga,Al)₂, Y(Ga,Si)₂ and Y(Ga,Ge)₂ Solid Solutions with Structure of AlB₂ Type - Semen’ko, M.P.; Bilyavina, N.M.; Nakonechna, O.I. (Металлофизика и новейшие технологии, 2017)
Electrical properties (resistivity and temperature coefficient of resistivity) of the Y(Ga,Al)₂, Y(Ga,Si)₂ and Y(Ga,Ge)₂ solid solutions are studied using the model coatings deposited on mica substrate. Analysis of temperature dependences of the resistivity reveals that YGa₂ compound as well as the solid solutions on its base possess a metallic conductivity. Substitution of a certain part of the gallium atoms in YGa₂ compound belonging to AlB₂-type structure with germanium, silicon or aluminium atoms leads to decrease of resistivity in the Ga → Ge → Si → Al series that may be caused by both the nature of atoms themselves and technological parameters of coatings’ preparation (primarily, by their homogeneity).